Laporan pendekatan kajian: pelan pengurusan pembangunan persisir pantai Padang Mat Sirat-Ayer Hangat, Langkawi, Kedah - Asmawi, M. Zainora; Zainal, Megat Sahrir; Mohd Saad, Nor Shah; Mohamad, Md. Zahar; Razak, Khamarrul Azahari; Che Hasan, Rozaimi; Ujang, Kamaruzaman; Abidin, Suriani; Mohamed, Mohd Zin (PLAN Malaysia Pejabat Projek Zon Utara, 2020)
This report of study approach addresses largely on the fundamental aspect of the sectoral studies, i.e. objectives, scopes, technique of analysis and outcome-mainly is about the research methodology of the sectoral studies involved in the whole framework of the study. The delivery of the study approach will be further addressed in analysis/technical report and proposal report.